2006
DOI: 10.1007/s10681-006-9133-4
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis for grain weight in common wheat

Abstract: Quantitative trait loci (QTL) analysis for grain weight (GW = 1000 grain weight) in common wheat was conducted using a set of 100 recombinant inbred lines (RILs) derived from a cross 'Rye Selection 111 (high GW) × Chinese Spring (low GW)'. The RILs and their two parental genotypes were evaluated for GW in six different environments (three locations × two years). Genotyping of RILs was carried out using 449 (30 SSRs, 299 AFLP and 120 SAMPL) polymorphic markers. Using the genotyping data of RILs, framework linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
48
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 30 publications
9
48
1
3
Order By: Relevance
“…However, none of the individual QTL was detected in both populations. Wang et al, 1999;Kulwal et al, 2004;2005a;Yang et al, 2005;Kumar et al, 2007 PIII PHST Single-locus (CIM) QTL Cartographer Wang et al, 2004;Kulwal et al, 2005b PIV GW Single-locus (SMA, CIM) QTL Cartographer Wang et al, 2004;Kumar et al, 2006 GPC: Grain protein content; PHST: Pre-harvest sprouting tolerance; GW: Grain weight; SMA: Single marker analysis, SIM: Simple interval mapping, CIM: Composite interval mapping, MCIM: Multiple-trait composite interval mapping M-QTL: In each of the two mapping populations, 5 M-QTL for GPC were detected, which accounted for a mere 7.22% (PII) to 7.24% (PI) of the phenotypic variation. The desirable alleles for high GPC were distributed in both the parents of the two populations studied.…”
Section: Qtl Analysis For Grain Protein Content (Gpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of the individual QTL was detected in both populations. Wang et al, 1999;Kulwal et al, 2004;2005a;Yang et al, 2005;Kumar et al, 2007 PIII PHST Single-locus (CIM) QTL Cartographer Wang et al, 2004;Kulwal et al, 2005b PIV GW Single-locus (SMA, CIM) QTL Cartographer Wang et al, 2004;Kumar et al, 2006 GPC: Grain protein content; PHST: Pre-harvest sprouting tolerance; GW: Grain weight; SMA: Single marker analysis, SIM: Simple interval mapping, CIM: Composite interval mapping, MCIM: Multiple-trait composite interval mapping M-QTL: In each of the two mapping populations, 5 M-QTL for GPC were detected, which accounted for a mere 7.22% (PII) to 7.24% (PI) of the phenotypic variation. The desirable alleles for high GPC were distributed in both the parents of the two populations studied.…”
Section: Qtl Analysis For Grain Protein Content (Gpc)mentioning
confidence: 99%
“…Two of 3 QTL (QGw.ccsu-2B.1 and QGw.ccsu-7A.1) were definitive and were detected in at least 4 different environments and also in the pooled environment. The individual QTL explained 9.06% to 19.85% phenotypic variation (Kumar et al, 2006).…”
Section: Qtl Analysis For Grain Weight (Gw)mentioning
confidence: 99%
“…In earlier studies, genomic regions associated with kernel weight and dimensions have been identified using monosomic (Giura and Saulescu 1996;Varshney et al 2000) and QTL analysis (Campbell et al 1999;Ammiraju et al 2001 andDholakia et al 2003;Kumar et al 2006;Breseghello and Sorrells 2007). Breseghello and Sorrells (2006) studied the association of these kernel traits with simple sequence repeat (SSR) markers in a collection of wheat cultivars, whereas Röder et al (2008) performed fine mapping of a grain weight QTL at the telomeric region of chromosomal arm 7DS.…”
Section: Introductionmentioning
confidence: 99%
“…Giura and Saulescu, 1996;Varshney et al, 2000 ) ‫کیو.تی.ال‬ ‫تجزیه‬ ‫و‬ ( Ammiraju et al, 2001 and2004;Dholakia et al, 2003;Kumar et al, 2006;Sorrells, 2006 and Campbell et al, 1999;Perretant et al, 2000;Galande et al, 2001;Igrejas et al, 2002;Narasimhamoorthy et al, 2006 …”
mentioning
confidence: 99%